Penerapan Asas Itikad Baik dalam Perjanjian Pembiayaan Konsumen (Studi pada Perusahaan Pembiayaan di Kota Bukittinggi) - Rusli, Benni (Pagaruyuang Law Journal, 2019)
This study discusses the aplitation of good faith in the process to make agreements, and barriers to what is found in its applications and any effort taken to overcome barriers to the application of in good faith. This study uses sociology juridical approach, with methods of collecting data such as; documents, deed of consumer financing agreement, interviews with informants, the data were analyzed qualitatively that by connecting with legislation, jurisprudence and expert opinion. The Research found that applying the principle of good faith has not been fully carried out by a Creditor that is in the sense of subjective, honesty to not conceal material facts and the obligation to explain material facts to prospective debito and debofors were also not in good faith the obligations in the form carefully examine the material facts in financing agreement, barriers found in the form of briet negotiation process until the signing of the agreement, the procedures prescribed consumer finance. Companies limit the opportunity to understand the facts material to the maximum. The lack of consumer willingness to question the material facts that will be agreed.